Effects of Hand Positions During Video Head-Impulse Test (vHIT) in Patients With Unilateral Vestibular Neuritis - Fu, Wei; He, Feng; Zhao, Ruoqi; Wei, Dong; Bai, Ya; Wang, XiaoMing; Han, JunLiang (Frontiers in Neurology, 2018)
Objective: The aim of this study was to identify the effects of hand positions (head and jaw) on the video head impulse test (vHIT). Methods: 86 healthy volunteers and 67 patients with unilateral vestibular neuritis(UVN) were recruited for this study. Different hand positions (head and jaw) were used for horizontal semicircular canals vHIT of healthy volunteers and UVN patients. All the obtained horizontal vHIT gains were analyzed. Results: Whether healthy volunteers or UVN patients, when horizontal vHIT were performed with head hand position, the number of head impulses which produced overhigh VOR gains were more than the jaw hand position(p<0.01). And gains were lower in using the jaw hand position than that in using the head hand position(p<0.05). However, there was no significant difference in mean head velocity between the two hand positions (p>0.05).Furthermore, using head hand position has greater chance to elicit the UVN patients of normal horizontal vHIT gains but with refixation saccades than using jaw hand position(p=0.04). Conclusion: The jaw hand position can increase the accuracy of vHIT to determine the lesion side.